Aquaculture Perspective of Multi-Use Sites in the Open Ocean: The Untapped Potential for Marine Resources in the Anthropocene - Buck, Bela H.; Langan, Richard (Springer Nature, 2017)
marine; freshwater; offshore engineering; water policy; governance